Identification of long-lived proteins in the mitochondria reveals increased stability of the electron transport chain - Krishna, Shefali; Arrojo e Drigo, Rafael; Capitanio, Juliana S.; Ramachandra, Ranjan; Ellisman, Mark; Hetzer, Martin W. (Developmental cell, 2021)
In order to combat molecular damage, most cellular proteins undergo rapid turnover. We have previously identified large nuclear protein assemblies that can persist for years in post-mitotic tissues and are subject to age-related decline. Here, we report that mitochondria can be long lived in the mouse brain and reveal that specific mitochondrial proteins have half-lives longer than the average proteome. These mitochondrial long-lived proteins (mitoLLPs) are core components of the electron transport chain (ETC) and display increased longevity in respiratory supercomplexes. We find that COX7C, a mitoLLP that forms a stable contact site between complexes I and IV, is required for complex IV and supercomplex assembly. Remarkably, even upon depletion of COX7C transcripts, ETC function is maintained for days, effectively uncoupling mitochondrial function from ongoing transcription of its mitoLLPs. Our results suggest that modulating protein longevity within the ETC is critical for mitochondrial proteome maintenance and the robustness of mitochondrial function. [Display omitted] •Mitochondria in the mouse brain are long lived and show considerable age mosaicism•Mitochondria contain many LLPs as part of protein complexes•LLPs in the electron transport chain show increased stability within supercomplexes•Longevity of LLP COX7C preserves oxphos function despite transcriptional decline Krishna et al. discover that mitochondria in neurons and muscle fibers exhibit slow turnover and contain many long-lived proteins that can be part of large protein complexes. The longevity of these proteins in the electron transport chain can maintain oxphos complex assembly and mitochondrial function despite their transcriptional decline.